The conflict over the conflict : the Israel/Palestine campus debate - Stern, Kenneth S. 1953- (New Jewish Press, 2020)
Inhaltsverzeichnis: Thinking about Thinking -- Zionism and 1948 -- Free Speech and Academic Freedom -- Durban and Its Aftermath -- The Academic Boycott of Israel -- Stopping and Chilling Speech; Heckler's Veto, Legal Threats -- The Antisemitism Awareness Act -- Blueprint for Rational Campus Discussion on Israel and Palestine